The effect of N-acetylcysteine in the nucleus accumbens on neurotransmission and relapse to cocaine - Kupchik, Yonatan M. (2011)
BACKGROUND: Relapse to cocaine-seeking has been linked with low glutamate in the nucleus accumbens core (NAcore) causing potentiation of synaptic glutamate transmission from prefrontal cortex (PFC) afferents. Systemic N-acetylcysteine (NAC) has been shown to restore glutamate homeostasis, reduce relapse to cocaine-seeking and depotentiate PFC-NAcore synapses. Here we examine the effects of NAC applied directly to the NAcore on relapse and neurotransmission in PFC-NAcore synapses, as well as the involvement of the metabotropic glutamate receptors (mGluRs) mGluR2/3 and mGluR5. METHODS: Rats were trained to self-administer cocaine for 2 weeks and following extinction received either intra-accumbens NAC or systemic NAC 30 or 120 minutes, respectively, prior to inducing reinstatement with a conditioned cue or a combined cue and cocaine injection. We also recorded postsynaptic currents using in vitro whole cell recordings in acute slices and measured cystine and glutamate uptake in primary glial cultures. RESULTS: NAC microinjection into the NAcore inhibited the reinstatement of cocaine-seeking. In slices, a low concentration of NAC reduced the amplitude of evoked glutamatergic synaptic currents in the NAcore in a mGluR2/3-dependent manner, while high doses of NAC increased amplitude in a mGluR5-dependent manner. Both effects depended on NAC uptake through cysteine transporters and activity of the cysteine/glutamate exchanger. Finally, we showed that by blocking mGluR5 the inhibition of cocaine-seeking by NAC was potentiated. CONCLUSIONS: The effect of NAC on relapse to cocaine-seeking depends on the balance between stimulating mGluR2/3 and mGluR5 in the NAcore, and the efficacy of NAC can be improved by simultaneously inhibiting mGluR5.